Effects of various biomechanical errors on computed joint kinetics values - Kim, H. Y.; Sakurai, S.; Ahan, J.-H.; Doyo, W.; Ando, F.; Shimokata, H. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Alterations of the ankle JCL and CoP in the anterior-posterior direction largely affected the values of dorsiflexion/plantarflexion moment of ankle joint. Changes of the magnitude of the moments resulting from the difference in BSP values were small in every direction. The frontal/horizontal-plane moments calculated with CoP errors were much larger than those with BSP and JCL errors. As for the frontal-plane moment with CoP errors in the medial-lateral direction, not only the magnitude of moment value but also a different timeseries curve patterns were observed.